Pengaruh Pendidikan Kesehatan terhadap Pengetahuan Ibu Post Partum Tentang ASI Eksklusif - Suryaningsih, Chatarina (Jurusan Keperawatan FIKES UNSOED, 2013)
This research to find out if the influence of health education against knowledge mother post partum about exclusive breast feed in Melati room 1 Sariningsih Hospital Bandung. This research adopts pre-experimental study with approach one group pretest and posttest design. Instrument in this research used a questionnaire with 20 questions. The technique of data collection used purposive sampling according to criteria inclusion ana exclusion. Population in this research is all mother post partum. The sample in this research as many as 20 respondents. Result of research obtained value mean knowledge before heatth education is 10.59 while the value mean health education is 16.75. The different value is 5.800 with standard deviations 2.668 and seen from the value of p value 0.000. There is can be concluded that health education can affect knowledge mother post partum about exclusive breast feed. Therefore expected the continuity in run the granting health education by the exertion of post partum knowledge about exclusive breastfeed.